Social change in developing areas. A reinterpretation of evolutionary theory. Ed. by H.R. Barringer, G.I. Blanksten and R.W. Mack. [With contribs of D.T. Campbell, A.E. Emerson, M.E. Opler a.o.] (Schenkman, 1965)
With indices and tabs.